INTERACTIVE MOBILE-BASED EDUCATIONAL GAME TO INTRODUCE WASTE SORTING USING MULTIMEDIA DEVELOPMENT LIFE CYCLE (MDLC) METHOD - Faisal Reza Pradhana; Aziz Musthafa; Agustin Amalia Permadani (JIKO (Jurnal Informatika dan Komputer), 2025)
Increasing public awareness of waste management is an important focus in order to maintain environmental sustainability. However, the level of understanding about waste sorting is still minimal, especially among children. To overcome this lack of literacy, a technology-based educational game was developed which aims to introduce the concept of waste sorting to children. This research aims to design and develop an interactive and fun educational game application to improve children's understanding of the importance of waste management. Using iterative development techniques, this app is designed to provide an effective learning experience and support the formation of positive habits from an early age. The application is designed following the stages of the Media Development Life Cycle (MDLC) method. The game media has gone through several tests, namely software functionality tests with 100% results, learning material tests by distributing questionnaires to material experts with an average rating of 90%, tests to learning media experts with an average rating of 93.33%, and tests to potential users with an average rating of 78.57%. The results of the research are expected to contribute significantly to educating the younger generation, especially children, about the importance of maintaining environmental cleanliness through wise waste management. This application is expected to be an innovative learning tool that supports environmental sustainability.